“Votar é muito mais sério que mudar de canal de televisão”: a televisão na eleição presidencial de 1989 - Estevão, Lucas Cavalcante (2024)
The aim of this paper is to analyze Brazil’s 1989 presidential campaign and its electoral strategies within television media. The use of television as a medium for producing, reproducing, and disseminating national agendas during campaign ads, known as Free Electoral Political Broadcasts (Horário Gratuito Político Eleitoral), became a crucial tool for aligning the propagandistic content with the political messaging of presidential candidates, which helped creating a landscape for the appropriation of political concepts that resurfaced in the public arena, such as democracy, citizenship, and rights, in the post-Civil-Military Dictatorship period (1964-1985). The audiovisual productions of the presidential campaign highlighted the importance of voting through the Free Electoral Political Broadcasts, presenting viewers with the expressions and political-party positions of the New Republic. Analyzing the electoral programs offers us opportunities for historical reflection on the images, discourses, and social reproductions disseminated on television in the 1980s. The expanded scope of audiovisual advertisements enable an analysis of production contexts, political party and candidate positions, and consumption formats, offering insights into emerging socioeconomic demands and visual trends. In this sense, this paper examines television's role in the political formation of Brazilians and the reproduction of audiovisual strategies in promoting presidential campaigns during the 1989 election.